Prevalence of Sleep Disordered Breathing (SDB) and risk factors in Malay, Chinese and Indian school children in Malaysia - Mohd. Zainudin, Norzila; Ab Rahman, Jamalludin; AW, Norrashidah; Kassim, Asiah; Abdul Latif, Hasniah; Awang, Rus Anida; Abdullah, Ahmad Fadzil; Zainal, Ramli; Hussain, Samsinah (Malaysian Paediatrics Association, 2010)
Introduction: The prevalence of SDB and contributing risk factors in Malaysian school children is unknown. Aim: To determine the prevalence of parental report of SDB and risk factors among school children aged 6 to 10 years old in three primary schools using the translated University Michigan Paediatric Sleep Questionnaire (UMPSQ). Method: All children whose parents responded to the questionnaire and consented undergone a physical examination documenting height, weight, skin-fold thickness, neck and abdominal circumference, tonsillar size, nostril examination and presence of micrognathia or retrognathia. Results: Data were analysed on a total of 1459 sets of questionnaires. The prevalence of parental reporting of SDB among Sekolah Rendah Jenis Kebangsaan(SRJK) school children was 15%, Sekolah Rendah Jenis Kebangsaan Cina (SJKC) 13.7% and Sekolah Rendah Jenis Kebangsaan Tamil (SJKT) 15.7%. Obesity is a risk factor of SDB in all schools. Gender is a risk factor in SRJK and SJKC school children. Increased neck and abdominal circumference, increased skin fold measurements and enlarged tonsils are significant risk factors only in SRJK school children. Conclusion: Different schools representing different ethnicity may have different risk factors of SDB.